Design of fuzzy dynamic decoupler for a class of two-inputs two-outputs nonlinear systems - Król, Szymon; Dworak, Paweł (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper deals with the problem of designing a dynamic decoupler for a class of two-inputs two-outputs nonlinear MIMO systems with experimentally modeled dynamics. The work describes the well-known linear theory of dynamic decoupling of TITO plants and discusses problems related to its application to nonlinear systems. The solution of constructing a fuzzy dynamic decoupler with two possible approaches is proposed. The paper gives a practical example of the synthesis of such a system for the air heater, which is an example of nonlinear thermal plant.